Differences Of Students’ Mathematical Communication Skills Through Contextual Teaching Learning With Problem Based Learning Model - Anim Anim; Eva Margaretha Saragih (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to determine the differences in mathematical communication skills of students in the material opportunities by using PBL and CTL learning models in class X of the Al-Istiqomah Private Vocational School in the Regency of Java. This type of research is semi-experimental. The population in this study were all students of class X of Private Al-Istiqomah Vocational School, Regency of Java. The research sample was 2 classes. The results of the research obtained F_count> F table which is 15.31> 3.99, so to test the hypothesis it can be concluded that rejecting H0 means thank Ha, there are differences in mathematical communication skills of students taught using problem based learning models with students taught using Contextual Teaching learning models Lerning. There are differences in mathematical communication skills of students taught using a problem-based learning model compared to students who are taught using the 9% Contextual Teaching Lerning learning model